ENHANCING LANGUAGE ACQUISITION THROUGH SHADOWING: A STUDY ON PRONUNCIATION FLUENCY AND LISTENING COMPREHENSION - Shohista Yusupova Otabek kizi; Khazratkulova Ezoza Ismat kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This study investigates the role of shadowing in enhancing language acquisition, focusing on three key aspects: pronunciation, fluency, and listening comprehension. Shadowing is a language learning technique where learners mimic the speech of native speakers, attempting to replicate the pronunciation, rhythm, and intonation of the speaker. The research examines how shadowing can improve pronunciation accuracy, increase fluency in speech, and develop better listening comprehension. A group of language learners participated in a series of shadowing exercises, and their progress was measured in terms of pronunciation clarity, speed and naturalness of speech, and their ability to comprehend spoken language. Results showed that regular practice of shadowing significantly improved the learners’ pronunciation and fluency. Additionally, the technique was found to enhance listening comprehension by exposing learners to authentic speech patterns. This  study concludes that shadowing is an effective method for improving key language skills and can be a valuable tool in the language learning process.